Temporal and age-dependent effects of haptoglobin deletion on intracerebral hemorrhage-induced brain damage and neurobehavioral outcomes - Leclerc, Jenna L (Exp Neurol, 2019)
Intracerebral hemorrhage (ICH) is a devastating stroke subtype and the presence of extracorpuscular hemoglobin (Hb) exacerbates brain damage. Haptoglobin (Hp) binds Hb, which prevents its oxidation and participation in neurotoxic reactions. Multiple studies have investigated the role of Hp under conditions of intravascular hemolysis, but little is known about its role in the brain and following ICH where extravascular hemolysis is rampant. Young and aged wildtype and Hp(−/−) mice underwent the autologous blood or collagenase ICH model. Early after ICH, Hp(−/−) mice display 58.0±5.6% and 36.7±6.9% less brain damage in the autologous blood and collagenase ICH models, respectively. In line with these findings, Hp(−/−) mice display less neurological deficits on several neurobehavioral tests. Hp(−/−) mice have less Perl’s iron content, HO1 expression, and blood brain barrier dysfunction, but no difference in brain Hb content, astrogliosis and angiogenesis/neovascularization. At the later endpoint, the young cohort displays 27.8±9.3% less brain damage, while no difference is seen with the aged cohort. For both cohorts, no differences are seen in HO1 levels or iron accumulation, but young Hp(−/−) mice display less thalamic astrogliosis and striatal microgliosis. This study reveals that the presence or absence of Hp exerts important time- and age-dependent influences on ICH outcomes.